Enhanced visualization of the flat landscape of the Cambridgeshire Fenlands - Pritchard, Oliver G.; Farewell, Timothy S.; Hallett, Stephen H. (Wiley, 2015)
The Fenlands of East Anglia, England, represent a subtle landscape, where topographic highs rarely exceed 30 m above sea level. However, the fens represent an almost full sequence of Quaternary deposits which, together with islands of Cretaceous and Jurassic outcrops, make the area of geological importance. This feature discusses the advantages of using 3D visualization coupled with high-resolution topographical data, over traditional 2D techniques, when undertaking an analysis of the landscape. Conclusions suggest that the use of 3D visualization will result in a higher level of engagement, particularly when communicating geological information to a wider public.